The Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai di Kantor Desa Salassae Kec. Bulukumpa Kab. Bulukumba - Irham Irham; Azwar Wijaya Syam (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
ABSTRACT This study aims to determine and analyze the effect of work motivation on employee performance in the village office of Salassae Kec. Bulukumpa Regency. Bulukumba The type of research used is descriptive quantitative, in which the writer describes the results of observations and analyzes the data obtained in the field. To determine the effect of work motivation variables on employee performance, a linear analysis of the dependent and independent variables was carried out. The dependent variable (Y) in this study is performance, while the independent variable (X) is work motivation. After analyzing and discussing the problem, the authors draw conclusions from the results of the regression data processing above explaining that the value of the regression coefficient of motivation (X) on employee performance (Y) is 0.321 (32.1%), this indicates that motivation (X) has the influence on employee performance (Y) is equal to 32.1% meaning that if there is motivation (X) of 100%, it will increase employee performance (Y) by 32.1%, and vice versa Keywords: Work Motivation, Work Motivation.